1993
DOI: 10.1002/ijc.2910540325
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human malignant melanoma tumor spheroids with endothelium and reconstituted basement membrane: Modulation by RGDS

Abstract: Tumor-cell extravasation involves sequential adhesive interactions with vascular endothelium and the subendothelial basement membrane. We have established a 3-dimensional model in vitro to simulate these events and to elucidate targets of the anti-cell-adhesive synthetic peptide RGDS. Tumor spheroids of the melanoma cell line ST-ML-12 served as models of tumor-cell emboli and were transferred onto human umbilical vein endothelial cells. To imitate the vascular anatomy, the latter were grown on reconstituted ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
2
23
0
2
Order By: Relevance
“…Ffrench-Constant and Hynes [43] showed that fibronectin may play a role in the migration of mesenchymal cells of the area vasculosa and endocardial cushion cells. The results presented by Offner et al [44] show that fibronectin is also important for the migration of malignant melanoma cells. Thus, over-expression of matrixdegrading enzymes and interactions with several components of the extracellular matrix by the glioma cells themselves or induced by hypoxia might contribute to the tumour cell spread presented here.…”
Section: Discussionmentioning
confidence: 87%
“…Ffrench-Constant and Hynes [43] showed that fibronectin may play a role in the migration of mesenchymal cells of the area vasculosa and endocardial cushion cells. The results presented by Offner et al [44] show that fibronectin is also important for the migration of malignant melanoma cells. Thus, over-expression of matrixdegrading enzymes and interactions with several components of the extracellular matrix by the glioma cells themselves or induced by hypoxia might contribute to the tumour cell spread presented here.…”
Section: Discussionmentioning
confidence: 87%
“…To gain insights into the mechanisms underlying lymphatic bulk invasion, we have adapted a reductionistic in vitro assay (25,26) that mimics some features of the in vivo situation. In this system, tumor cell spheroids corresponded to invasive tumor aggregates in vivo, and in lieu of intrametastatic lymphatic vessels, we used monolayers of dermal lymphatic endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…We used an in vitro coculture system to analyze the mechanisms of tumor cell-mediated disruption of lymphatic vessels. This employed spheroids (25,26) of MCF7 mammary carcinoma cells to reproduce the clusters of cells seen in tumor emboli in vivo. MCF7 cell spheroids remained stable Table 1 Characterization of tumors and patients' outcome …”
Section: Intrametastatic Lymphatic Carcinosismentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of cells was carried out by a modified medium as the mesothelial cells (see above). method previously described elsewhere [21]. Briefly, small biopsies (approximately 3 cm 3 ) of omental tissue were rinsed Cancer Cells in phosphate-buffered saline (PBS), transferred to a 0.05% solution of collagenase I (Worthington, Boehringer-MannFor experiments, HPMCs and ovarian cancer cells were heim) and allowed to float for 1.5-2 hr at 37ЊC.…”
Section: Introductionmentioning
confidence: 99%